2016
DOI: 10.7196/samj.2016.v107.i1.11226
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in a cohort of neonates at Groote Schuur Hospital, Cape Town, South Africa

Abstract: Background. Severe retinopathy of prematurity (ROP) can cause blindness. Before 2016, resource limitations precluded routine screening for ROP at Groote Schuur Hospital (GSH), Cape Town, South Africa. Previous pilot studies at GSH found no patients with ROP requiring treatment; however, improved preterm infant survival may affect the prevalence. Objectives. To determine the prevalence and severity of ROP, describe potential risk factors, and assess the feasibility of ROP screening. Methods. Infants with a birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 5 publications
1
4
1
5
Order By: Relevance
“…The incidence of ROP in our sample (48.19%) is higher than rates reported in studies from other middle income countries like India (Eastern India 33.2% [22], Northern India 26.6% [23], and rural outreach centers 22.39% [24]), Turkey (30% [25] and 27% [26]), South Africa (29.6% [27]), Iran (23.5% [28]), Palestine (23.5% [29]), and Botswana (11% [30]). The incidence of AP-ROP (8.7%) is also beyond the high end of the spectrum of rates reported in the literature that range from 0.11-5% [6].…”
Section: Discussioncontrasting
confidence: 69%
“…The incidence of ROP in our sample (48.19%) is higher than rates reported in studies from other middle income countries like India (Eastern India 33.2% [22], Northern India 26.6% [23], and rural outreach centers 22.39% [24]), Turkey (30% [25] and 27% [26]), South Africa (29.6% [27]), Iran (23.5% [28]), Palestine (23.5% [29]), and Botswana (11% [30]). The incidence of AP-ROP (8.7%) is also beyond the high end of the spectrum of rates reported in the literature that range from 0.11-5% [6].…”
Section: Discussioncontrasting
confidence: 69%
“…Transfusion of RBCs appears to be a risk factor for the development of ROP. 5,11,20,39,40,65,82,86,101,102,106,116,122,123,137,143,148,150,152,167,180,202,207,208,220,229,246,257,283,315,334,346,348,356,367,389,414 Four randomized controlled trials and a meta-analysis on the effect of transfusion protocols suggest the amount of transfusion may not be associated with ROP. 42,56,72,112,214…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…Neonatal sepsis is among the most frequently identified risk factors for any ROP and severe ROP. 5,10,14,23,35,57,65,68,114,137,143,149,150,152,205,208,220,229,235,245,249,257,263,264,266,271,277,283,301,309,315,362,367,377,391,414,423 It has been suggested that perinatal infection and inflammation may play important roles in ROP. 91 A New York state cohort study reported that the presence of neonatal sepsis was associated with an elevated risk of ROP.…”
Section: Alternative Risk Factorsmentioning
confidence: 99%
“…En este estudio, la retinopatía en general se presentó en el 53.9% de los casos, lo cual concuerda con los resultados de otros países con ingresos medios 33 . Sin embargo, los resultados de diversos países de la Red Internacional para la Evaluación de los Resultados de los recién nacidos indican tasas del 25.2 al 91% para cualquier ROP, en un total de 48,087 lactantes de 24-27 SDG incluidos en el análisis 34 .…”
Section: Discussionunclassified
“…En cambio, en el estudio de Guadalajara, el porcentaje aumenta al 30.3% si se analizan únicamente los casos de retinopatía. En general, diversos resultados refieren una media del 50% y un estadio 3 del 1.5 al 14% para todas las ROP 7,8,[32][33][34][38][39][40] .…”
Section: Discussionunclassified